Engineering Electronic Structure of Stannous Sulfide by Amino‐Functionalized Carbon: Toward Efficient Electrocatalytic Reduction of CO2 to Formate. Issue 8 (29th January 2020) - Chen, Zhipeng; Zhang, Xinxin; Jiao, Mingyang; Mou, Kaiwen; Zhang, Xiangping; Liu, Licheng
Abstract: Engineering electronic structure to enhance the binding energies of reaction intermediates in order to achieve a high partial current density can lead to increased yield of target products. Herein, amino‐functionalized carbon is used to regulate the electronic structure of tin‐based catalysts to enhance activity of CO2 electroreduction. The hollow nanotubes composed of SnS (stannous sulfide) nanosheets are modified with amino‐functionalized carbon layers, achieving a highest formate Faraday efficiency of 92.6% and a remarkable formate partial current density of 41.1 mA cm −2 (a total current density of 52.1 mA cm −2 ) at a moderate overpotential of 0.9 V versus reversible hydrogen electrode, as well as a good stability. Density functional theory calculations demonstrate that the superior activity is attributed to the synergistic effect among SnS and Aminated‐C in increasing the adsorption energies of the key intermediates and accelerating the charge transfer rate. Abstract : Engineering the electronic structure of stannous sulfide nanosheets by amino‐functionalized carbon for the highly efficient electrocatalytic reduction of CO2 to formate, achieves a remarkable formate partial current density and a high formate Faraday efficiency simultaneously.